2022
DOI: 10.1021/acs.jafc.2c05284
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Rapid Detection Techniques for Pesticide Residue: A Review

Abstract: As an important chemical pollutant affecting the safety of agricultural products, the on-site and efficient detection of pesticide residues has become a global trend and hotspot in research. These methodologies were developed for simplicity, high sensitivity, and multiresidue detection. This review introduces the currently available technologies based on electrochemistry, optical analysis, biotechnology, and some innovative and novel technologies for the rapid detection of pesticide residues, focusing on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 194 publications
0
27
0
Order By: Relevance
“…In recent years, food safety has gathered considerable attention owing to the continuous occurrence of food contamination incidents. Owing to this reason, the present work also explores the potential of PPESI-MS in determining different pesticides in fluidic samples such as milk and orange juice. After investigating the performance of PPESI-MS, it was found that the packed adsorbent type significantly impacted the analysis sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, food safety has gathered considerable attention owing to the continuous occurrence of food contamination incidents. Owing to this reason, the present work also explores the potential of PPESI-MS in determining different pesticides in fluidic samples such as milk and orange juice. After investigating the performance of PPESI-MS, it was found that the packed adsorbent type significantly impacted the analysis sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Pesticide toxicity in the soil can have significant environmental and agricultural impacts. The presence of pesticides in soil has detrimental effects such as soil degradation, nontarget effects, disruption of nutrient cycling, and soil erosion via the reduction of soil stability [ 8 ].…”
Section: Pesticide Detection and Toxicitymentioning
confidence: 99%
“…Through using Au–S bonds in an electrochemical biosensor, Lin et al were able to identify chlorpyrifos in fruit samples with a LOD of 36 ng L −1 [ 17 ]. Studies using AuNMs have shown strong specificity and sensitivity for chlorpyrifos, isocarbophos carbamate, and methomyl, with LOD ranging from 70 × 10 −3 to 2.48 × 10 3 ng L −1 [ 8 ]. AgNM has a wide surface ratio, elevated electron transport efficacy, and easy availability which makes it more suitable for incorporating into biosensor design.…”
Section: Nanomaterials Used In Biosensing Applicationsmentioning
confidence: 99%
“…Rapid on-site detection using portable devices is becoming increasingly desirable in agricultural, clinical, environmental, forensic, and pharmaceutical analyses. [1][2][3][4][5] It enables quick decision-making in the field, which cannot be achieved by traditional analytical approaches. 6,7 The strategy has demonstrated a promising potential for outside-the-laboratory screening, dramatically reducing the number of samples needed to be transported to centralized laboratories for further confirmatory evaluation.…”
Section: Introductionmentioning
confidence: 99%